Correlation between anthropometric indices at birth and developmental delay in children 4-60 months - Amir AliAkbari, Sedigheh; Torabi, Fatemeh; Soleimani, Farin; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2012)
Correlation between anthropometric indices at birth and developmental delay in children 4-60 months Amir Ali Akbari, S.1* (MSM); Torabi, F.2 (MSM); Soleimani, F.3 (MD); Alavi Majd, H.4 (PhD) 1. Lecturer, Dept. of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 2. Alumnus, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 3. Pediatrician, Administrator of Pediatrics Neurorehabilitation Research Center, University of Social Welfare and Rehabilitation Sciences, Tehran, Iran. 4. Associate Professor, Dept. of Biostatistics, Faculty of Paramedical, Shahid Beheshti University of Medical Sciences, Tehran, Iran. Abstract Background and aim Advancements in medical knowledge and treatment modalities have resulted in increasing the survival rate of high risk infants. This increased number of survivors call attention to future development of these children. After infection and trauma, developmental and behavioral problems are the most common children medical problems. The aim of this study was to determine correlation between anthropometric indices at birth and developmental delay in children 4-60 months that were visited in health services centers affiliated to University of Medical Sciences in 2010. Materials and methods In this descriptive-corrolational study, 401 children 60-4 months that were visited in health services centers affiliated to University of Medical Sciences in 2010 were selected by multistage method. Anthropometric indices of children at birth were collected from their health care records and development status of children was measured by "Ages and Stages Questionnaire". Validity of 0/84 and reliability 0/94 were obtained from pervious study. Data were analyzed by SPPS v 18. Findings The results showed that the average age of children in normal group was 17/33±13/18 month and in developmental delay group was 29/92±19/19 month. Most gender in normal group was female (%56) developmental delay group was male (%55/2). In addition, there were no correlation between height and head circumference at birth and developmental delay. However, birth weight of children with developmental delay were four times lower than birth weight of normal developmental children (p = 0.004, OR = 4). Conclusion Factors that lead to intrauterine growth reduction will create many problems in the neonatal period. On the other hand, staying these infants in NICU is longer and lead to presenting disorders in child developmental process. Keywords: Anthropometric indices, Developmental delay, Child *Corresponding Author: Sedigheh, Amir AliAkbari. Lecturer, Dept. of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: asa_akbari@yahoo.com